Travessias na EJA: a extensão universitária como ponte do fazer, do aprender, do pensar - Camargo, Maria Rosa Rodrigues Martins De [UNESP]; Miguel, José Carlos [UNESP]; Zanata, Eliana Marques [UNESP] (Centro de Estudos Educação e Sociedade, 2015)
To articulate reflections on the production of knowledge in the field of Youth and Adult Education, EJA, in the dynamics of University extension courses, we focus on the Youth and Adult Education Program (Peja), developed at Universidade Estadual Paulista Júlio de Mesquista Filho (Unesp) since 2001. The objectives that organize the activities in the program are: assisting people with little or no instruction, and training educators and graduate students pursuing various Bachelor's degrees who work in teaching activities in various social institutions. The article refers to a systematic analysis of the material sources used in the intervention proposals and studies, based upon the cultural history with a focus on cultural practices, in language studies under the perspective of dialogue and the cultural-historical approach, the basis for the construction of objects of thought. Immersion in the sources brings to the surface issues that contribute to the reflection when constituting inherent subsidies to educational, cultural and political practices.

Para articular reflexões acerca da produção de conhecimento, no campo da Educação de Jovens e Adultos (EJA), na dinâmica da extensão universitária, focamos o Programa de Educação de Jovens e Adultos (Peja), desenvolvido na Universidade Estadual Paulista Júlio de Mesquita Filho (Unesp) desde 2001. Os objetivos que organizam a atuação no Programa são: o acompanhamento de pessoas pouco ou nada escolarizadas e a formação de educadores, graduandos em licenciaturas diversas que atuam nas atividades de ensino, em instituições sociais diversas. O artigo remete a uma análise sistemática das fontes materiais utilizadas nas propostas de intervenção e estudos, aportada na história cultural com foco nas práticas culturais, em estudos da linguagem na perspectiva da interlocução e na abordagem histórico-cultural, base para a construção de objetos de pensamento. A imersão nas fontes traz à superfície temas que contribuem para a reflexão ao constituírem-se em subsídios inerentes às práticas educacionais, culturais, políticas.
Crossing bridges at youth and adult education: sharing knowledge through university extension courses
Keywords: Youth and adult education; University extension courses; Shared knowledge; Knowledge production; Educação de jovens e adultos; Extensão universitária; Saberes compartilhados; Saberes produzidos